Efektivitas Program Q-Ris (Quick Response Code Indonesian Standard) Oleh Bank Indonesia Dalam Meningkatkan Transaksi Non-Tunai - Cristina M Manurung; Jelita Novianma Sipahutar; Afina Charolin; Zaki Edi Saputra; Hasyim Hasyim (Global Leadership Organizational Research in Management, 2024)
This study investigates the perception of the public's perception of cashless transactions, the implementation of the Quick Response Code Indonesian Standard (QRIS) by Bank Indonesia, and the impact of QRIS on the volume of cashless transactions as well as the challenges and opportunities for its development. volume of non-cash transactions as well as challenges and opportunities for its development. Methods qualitative method with a literature research approach was used. Data and information were collected from various reliable sources, such as scientific journals, books, and relevant articles. The results show that the implementation of QRIS has increased the adoption of cashless transactions, especially in 2022. This helps MSMEs as it speeds up their operations and expands their customer base. their customer base. However, infrastructure issues, uneven digital literacy, and security threats such as uneven digital literacy, and security threats such as fake QR code scams are the challenges faced. More efforts are needed to improve digital literacy literacy and developing adequate technological infrastructure to ensure the benefits of the benefits of QRIS can be enjoyed by all levels of society.